Pengaruh Live Streaming, Online Customer Review Dan Flash Sale Terhadap Keputusan Pembelian Produk Kosmetik Scarlett Whitening Di Tiktok Shop - Febriyanti, Alviyani; Ratnasari, Ina (Peneliti.net, 2024)
Digital marketing in Indonesia has enormous potential, because many consumers have switched to the digital world. Online marketing has generally been carried out by companies and individuals, through the use of digital information technology such as social media in the form of Facebook, Instagram, TikTok and so on. This study describes how consumers make purchasing decisions on a Scarlett Whitening cosmetic product at the Tiktok Shop which is influenced by Live Streaming, Online Customer Reviews, and Flash Sale. The purpose of this study was to analyze the effect of Live Streaming, Online Customer Reviews, and Flash Sale on the Purchase Decision for Scarlett Whitening cosmetic products at the Tiktok Shop. This research uses quantitative methods through descriptive and verification approaches. The data collected was taken using a questionnaire that had been distributed and obtained using SPSS 21. Respondents in this study were 170 users of Scarlett Whitening cosmetic products at the Tiktok Shop. After the data has been collected, the data is processed using a descriptive method to find out the value of the independent variable, either one variable or more (indipendent) without making comparisons, or linking it with other variables. While the verification approach is used to test the theory by testing the hypothesis.